Konstruování obrazu minulosti zaměřené na dětské adresáty: míšení stylů a žánrů - Hoffmannová, Jana (Stylistyka, 2019)
The monthly magazine Časostroj (Time Machine), published in the Czech Republic since 2011, is meant to enable “a fun journey into history” for readers aged 7–15. Several years ago, this magazine took 2nd place in a competition organised by the Czech Academy of Sciences for the popularisation of science. The paper considers how this specifically-profiled popularisation of history oscillates between academic (pedagogical, didactic), everyday communicative and “entertainment” styles, as well as how the entertainment function of language and texts is promoted in contemporary communication. Attention is devoted to the fact that in this popularising discourse – probably much more than in scholarly historiography – narration merges with commentary, and historical fiction has a specific use. The selection of topics and historical events is determined witha consideration of young readers, who are transported into history and directly integrated into past events. The magazine’s authors and editors engage their intended readers in continuous dialogue and maintain live contact with them. The paper also presents the various genres which appear in the magazine (from myths, legends and fables to comics, including, e.g. “historical detective stories”). It further recalls and accents everyday life in history in this popularising discourse and its connections to the gender perspective (female perspective), among others. Emphasis is also placed on the educational function of the texts – on how young readers are encouraged to be actively interested in history and to be independent thinkers (e.g. through alternative history).